Heroin use is associated with liver fibrosis in the Miami Adult Studies on HIV (MASH) cohort. (1st March 2021) - Baum, Marianna K.; Tamargo, Javier A.; Ehman, Richard L.; Sherman, Kenneth E.; Chen, Jun; Liu, Qingyun; Mandler, Raul N.; Teeman, Colby; Martinez, Sabrina S.; Campa, Adriana
Highlights: HIV and opioids increase risk for liver-related morbidity and mortality. We used highly-accurate magnetic resonance elastography to assess liver fibrosis. Heroin use was independently associated with increased risk for liver fibrosis. Misuse of prescription opioids was not associated with liver fibrosis. HIV and HCV were associated with liver fibrosis, even if virally suppressed. Abstract: Background: People who use opioids and people living with HIV (PLWH) are at increased risk for liver-related morbidity and mortality. Although animal models suggest that chronic opioid use may cause liver damage, research in humans is limited. We aimed to determine whether opioid use, particularly heroin, was associated with liver fibrosis. Methods: Cross-sectional analysis of 679 participants (295 HIV/HCV uninfected, 218 HIV mono-infected, 87 HCV mono-infected, 79 HIV/HCV coinfected) from the Miami Adult Studies on HIV (MASH) cohort. Liver fibrosis was assessed via magnetic resonance elastography (MRE) on a 3 T Siemens MAGNETOM Prisma scanner. Results: A total of 120 (17.7 %) participants used opioids. Liver fibrosis was present in 99 (14.6 %) participants and advanced liver fibrosis in 31 (4.6 %). Heroin use (N = 46, 6.8 %) was associated with HCV-seropositivity, smoking, misuse of prescription opioids, and polysubstance use. The use of heroin, but not misuse of prescription opioids, was significantly associated with liver fibrosis (OR = 2.77, 95 % CI: 1.18―6.50) compared to heroin non-users, after adjustment for confounders including excessive alcohol consumption, polysubstance use and HIV and HCV infections. Both HIV and HCV infections were associated with liver fibrosis, whether virally suppressed/undetectable or viremic. Conclusions: Heroin use was independently associated with increased risk for liver fibrosis irrespective of the use of other substances and HIV or HCV infections. Both HIV and HCV were associated with higher risk for liver fibrosis, even among those with suppressed or undetectable viral loads. The exact mechanisms for opioid-induced liver fibrosis remain to be fully elucidated.